On the diversity of law enforcement corporate culture (Academic Journal of Internal Affairs, 2017)
The author provides an overview of a comparative research ion the (different) corporate culture of law enforcement agencies, Police, Prison Services, Tax and Customs Administration, Disaster Management in Hungary.
Keywords: law enforcement; corporate culture; diversity